CHALLENGES FOR SPORT PEDAGOGY DUE TO THE INFLUENCE OF MARKETING ON CONTEMPORARY SPORT - Leandro de Melo Beneli; Marcelo Weishaupt Proni; Paulo Cesar Montagner (Journal of Physical Education)
ABSTRACT The basic motivation of this essay comes from the need to understand some relationships that are established in the teaching environment of sports for kids, from the transformations of contemporary sport. Our goal is to discuss the challenges to the pedagogical practice and the role of the sport educator face of changes in the sport-spectacle and its interface with sports marketing. The methodology was based on literature search in order to substantiate a theoretical discussion and build a discussion around the existing tensions between sport pedagogy and sports marketing. We concluded that it is vital that sport educators, when teaching children, include this theme in classes and educational practices, bearing in mind the importance of this content to the consolidation of cognitive and moral references, thus seeking to stimulate a broader understanding of the social significance of sports.